1992
DOI: 10.3102/00028312029002373
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Teach Through Collaborative Conversation: A Feminist Approach

Abstract: As part of a longitudinal research project on learning to teach literacy and as a personal quest to make her work as a teacher educator more supportive, this researcher arranged an ongoing conversation for members of three cohorts of preservice and beginning elementary teachers. The conversation was prompted by an interest in beginning teachers’ critical responses to the personal support for learning to teach that they receive from their teacher education programs. From the social, collaborative, and nonevalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…He attributed this attitude to the tendency of prospective teachers to see themselves in the role of nurturers. Beliefs about the importance of relationship building endure into the first years of teaching when new teachers often expend a great deal of energy trying to find ways to develop positive relationships with their students (Hollingsworth, 1992). In reviewing the research literature on learning to teach, Wideen et al (1998) concluded, "Beginning teachers value social and peer groups, positive self-concept, and helping behaviors" (p. 142).…”
Section: Prospective Teachers Beliefs About the Nature Of Teachingmentioning
confidence: 99%
“…He attributed this attitude to the tendency of prospective teachers to see themselves in the role of nurturers. Beliefs about the importance of relationship building endure into the first years of teaching when new teachers often expend a great deal of energy trying to find ways to develop positive relationships with their students (Hollingsworth, 1992). In reviewing the research literature on learning to teach, Wideen et al (1998) concluded, "Beginning teachers value social and peer groups, positive self-concept, and helping behaviors" (p. 142).…”
Section: Prospective Teachers Beliefs About the Nature Of Teachingmentioning
confidence: 99%
“…Research is establishing that women's modes of thought and women's methods of knowledge construction are different from those of their male counterparts (Belenky et al 1986). Women achieve higher levels of learning through collaborative processes and experiential learning than through passive assimilation (Hollingsworth 1992). The idea that collaborative learning is beneficial to women is supported by cultural feminism, which emphasizes a holistic and collective orientation to the world and work (Gilman 1988), as well as feminist epistemology, which considers experience as knowledge (Belenky et al 1986).…”
Section: Cultures That Support Womenmentioning
confidence: 99%
“…This program emphasized positive interdependence and collaboration among 4 first-year physical educators, 8 interns during a 3-month field experience, and 2 university supervisors. All participants agreed to reflect and encourage values consistent with a learning community model (Lieberman, 1996;Little & McLaughlin, 1993;Noddings, 1996) where all would be co-learners and dialogue would be informed by an ethic of care (Hollingsworth, 1992;Noddings, 1992). fy the impact of this program on the beginning teachers.…”
mentioning
confidence: 98%